A new coral reef mantis shrimp from the northwestern Indian Ocean, Gonodactylellus celosinus sp. nov. (Crustacea: Stomatopoda: Gonodactylidae) - Ahyong, Shane T. (Zootaxa, 2024)
The Indian Ocean coral reef mantis shrimp, Gonodactylellus demanii (Henderson, 1893), described from the Gulf of Mannar, southeastern India, was thought to range widely, from the northwestern Indian Ocean to the eastern Bay of Bengal, Burma. Reevaluation of G. demanii from throughout its purported range revealed that what was thought to be that species in the northwestern Indian Ocean represents a new species, formally named herein, Gonodactylellus celosinus sp. nov. Gonodactylellus demanii sensu stricto is now known only from the Bay of Bengal (southeastern India to Burma). The taxonomic issues within G. demanii have gone unnoticed until now because the original account was inadequate for recognition of the species and subsequent revisions did not revisit the type or topotypic material. Gonodactylellus demanii is figured alongside G. celosinus sp. nov. to facilitate their recognition.